Subjective Socioeconomic Status, Cognitive Abilities, and Personal Control: Associations With Health Behaviours - Kraft, Pål; Kraft, Brage; Hagen, Thomas; Espeseth, Thomas (Frontiers in Psychology, 2022)
Objective: To examine subjective and objective socioeconomic status (SSES and OSES, respectively) as predictors, cognitive abilities as confounders, and personal control perceptions as mediators of health behaviours. Design: A cross-sectional study including 197 participants aged 30–50 years, recruited from the crowd-working platform, Prolific. Main outcome measure: The Good Health Practices Scale, a 16-item inventory of health behaviours. Results: SSES was the most important predictor of health behaviours (beta = 0.19, p < .01). Among the OSES indicators, education (beta = 0.16, p < .05), but not income, predicted health behaviours. Intelligence (r = -0.16, p < .05) and memory (r = -0.22, p < .01) were negatively correlated with health-promoting behaviours, and the effect of memory was upheld in the multivariate model (beta = -0.17, p < .05). Personal control perceptions (mastery and constraints) did not act as mediators. Conclusion: SSES predicted health behaviours beyond OSES. The effect of socioeconomic indicators was not confounded by cognitive abilities. Surprisingly, cognitive abilities were negatively associated with health-promoting behaviours. Future research should emphasize SSES as a predictor of health behaviours. Delineating the psychological mechanisms linking SSES with health behaviours would be a valuable contribution towards improved understanding of socioeconomic disparities in health behaviours.